BTB-Zinc Finger Oncogenes Are Required for Ras and Notch-Driven Tumorigenesis in Drosophila. - Doggett, K.; Turkel, N.; Willoughby, L.F.; Ellul, J.; Murray, M.J.; Richardson, H.E.; Brumby, A.M. (PLoS ONE, 2015)
During tumorigenesis, pathways that promote the epithelial-to-mesenchymal transition (EMT) can both facilitate metastasis and endow tumor cells with cancer stem cell properties. To gain a greater understanding of how these properties are interlinked in cancers we used Drosophila epithelial tumor models, which are driven by orthologues of human oncogenes (activated alleles of Ras and Notch) in cooperation with the loss of the cell polarity regulator, scribbled (scrib). Within these tumors, both invasive, mesenchymal-like cell morphology and continual tumor overgrowth, are dependent upon Jun N-terminal kinase (JNK) activity. To identify JNK-dependent changes within the tumors we used a comparative microarray analysis to define a JNK gene signature common to both Ras and Notch-driven tumors. Amongst the JNK-dependent changes was a significant enrichment for BTB-Zinc Finger (ZF) domain genes, including chronologically inappropriate morphogenesis (chinmo). chinmo was upregulated by JNK within the tumors, and overexpression of chinmo with either RasV12 or Nintra was sufficient to promote JNK-independent epithelial tumor formation in the eye/antennal disc, and, in cooperation with RasV12, promote tumor formation in the adult midgut epithelium. Chinmo primes cells for oncogene-mediated transformation through blocking differentiation in the eye disc, and promoting an escargot-expressing stem or enteroblast cell state in the adult midgut. BTB-ZF genes are also required for Ras and Notch-driven overgrowth of scrib mutant tissue, since, although loss of chinmo alone did not significantly impede tumor development, when loss of chinmo was combined with loss of a functionally related BTB-ZF gene, abrupt, tumor overgrowth was significantly reduced. abrupt is not a JNK-induced gene, however, Abrupt is present in JNK-positive tumor cells, consistent with a JNK-associated oncogenic role. As some mammalian BTB-ZF proteins are also highly oncogenic, our work suggests that EMT-promoting signals in human cancers could similarly utilize networks of these proteins to promote cancer stem cell states.